Production of lignin from oil palm empty fruit bunch (EFB) as a mud thinner [electronic resource] - 425930 Taufik Nordin (2006)
Project Paper (Sarjana Muda Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2006